ANALISIS TERHADAP KETERBUKAAN INFORMASI PUBLIK PADA PERSEROAN TERBATAS YANG MELAKUKAN PENGUMPULAN DANA DONASI YANG DIDUGA DIGUNAKAN UNTUK PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY - Muhammad Rizqi; Chandra Yusuf (Jurnal Hukum Adigama, 2019)
Public Institution is a legal person under the Indonesian act number 14 year of 2008 about Public Information Openness. Under that act, Public Institution have an obligation to publish all the information on that regulation. Public Institution, under the Indonesian act of Public Information Openness means legislative, executive, judicative and any other institution who obtain operational funds from state income (ABPN) or regional income (APBD), public funds or foreign income. There’s an issue among Private Company and Public Information Commission, where the Private Company appointed as a Public Institution by the Judge from Indonesian Information Public Commission. There’s a gap on that dispute, because Private Company obeyed under the Indonesian act of Private Company number 40 year of 2007. The judge had consideration when decided Private Company to become a Public Institution, it’s because of that Private Company managed public donation and distribute that donation into several foundation. The other problem is the private company refused to be named as a Public Institution, so there’s no obligation for the private company to publish any information about the corporation.